Improving myoblast differentiation on electrospun poly(ε‐caprolactone) scaffolds. Issue 8 (17th May 2017) - Abarzúa‐Illanes, Phammela N.; Padilla, Cristina; Ramos, Andrea; Isaacs, Mauricio; Ramos‐Grez, Jorge; Olguín, Hugo C.; Valenzuela, Loreto M.
Abstract: Polymer scaffolds are used as an alternative to support tissue regeneration when it does not occur on its own. Cell response on polymer scaffolds is determined by factors such as polymer composition, topology, and the presence of other molecules. We evaluated the cellular response of murine skeletal muscle myoblasts on aligned or unaligned fibers obtained by electrospinning poly( ε ‐caprolactone) (PCL), and blends with poly(lactic‐ co ‐glycolic acid) (PLGA) or decorin, a proteoglycan known to regulate myogenesis. The results showed that aligned PCL fibers with higher content of PLGA promote cell growth and improve the quality of differentiation with PLGA scaffolds having the highest confluence at over 68% of coverage per field of view for myoblasts and more than 7% of coverage for myotubes. At the same time, the addition of decorin greatly improves the quantity and quality of differentiated cells in terms of cell fusion, myotube length and thickness, being 71, 10, and 51% greater than without the protein, respectively. Interestingly, our results suggest that at certain concentrations, the effect of decorin on myoblast differentiation exceeds the topological effect of fiber alignment. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2241–2251, 2017.